Escultura pública : poética do escultor Martins Correia - Coelho, José, 1948- (2015)
The Public sculpture, the work of this dissertation, has through the ages and history, and served as a barometer reference to the emancipation of civilizations. Through it we instinctively verbal approach, as a paradigm of a certain moment in the history of mankind. And it is in the public sculpture that is felt, his approach: he does not have the format of the mysterious statues of Easter Island in the Pacific, the Pyramids of the Nile in Egypt, or the circle of great monoliths of Stonehenge mentioned, pre structure - most important historical Europe, located in Britain. The aim of humility, create a methodology where your focus is to highlight the work of the Public Sculpture Sculptor Martins Correia, his poetic, time and artistic confrontation with his contemporary sculptors. Seeks to address one issue where public sculpture, has over the place busy times of citizenship coating is of particular interest, constituting metaphor, it refers to, as art-sculpture-public, defending cultural values. Creating tradition, reinforcing the aspect of artistic creation, required for rooting and enrichment of the people in the places where they live and dwell. Contributing to better social force, giving the possibility to deepen themes, which are providers of comprehensive information, which helps to combat desertification with various angles of various social issues of cultural interest. Thus the aim of this work is to search for the approach, conduct research, study and show that there is a role and a proper space for Public Sculpture, and can play, over countless generations, a key role in the collective identity of life community. The study presented in conceptual character, supported with texts, opinions of people who lived with the sculptor, unpublished photos and drawings, unknown to the public, subjects of study and research that objectively, recovery and provide arguments on the works and the person who was the Master Sculptor Martins Correia. To contribute to the clarification, visibility and Public Sculpture of the author, contrasting, proliferates, comparative and complementary, reinforcing its identity as a public reference insurmountable, the real meaning and cultural value in the history of Portuguese culture